KONTRIBUSI BATUR GLOBAL GEOPARK DALAM PEREKONOMIAN LOKAL DI KINTAMANI - Swasti Asparini Syahrijati, Putu (Jurnal Master Pariwisata (JUMPA), 2018)
The aims of this study are to determine the Batur Global Geopark, Kintamani, Bali, contribution to the economy of the local community, determine the ratio and changes in the standard of living that occur before and after Batur be the member of Batur Global Geoparks Network GGN, and the level of community participation in tourism activities in Batur Geopark. This study used a combination of qualitative and quantitative analysis. Research instrument was a questionnaire with accidental sampling technique and interviews with a sample set with a purposive. The results of this study stated that there was no change of standard of living as well as earnings before and after Batur Geopark designated as members of GGN. Lack of community participation is considered as a cause. Therefore, the article suggests a community-based tourism / community as a solution.